The Progressivity of the Qris Payment System in the Community: Perkembangan Sistem Pembayaran Qris di Masyarakat - Munawwarah, Siti; Khisan, Zariatul; Erawati, Desi; Nor Halisa (Transformatif, 2025)
The COVID-19 pandemic is a social change where people are forced to adapt, one of which is in the payment system. Bank Indonesia has established one of the digital payment systems, namely QRIS (Quick Response Code Indonesia Standard), to facilitate transaction payments easily, quickly, and securely. This study aims to measure the extent of the use of QRIS payments in the community. This research method uses qualitative research with data collection through a literature review associated with Talcott Parsons' theory. The results of this study show that the role of using the QRIS payment system among the public has shortcomings in terms of network connection and age factors. Among MSMEs, the QRIS payment system continues to increase due to the ease of transacting using one QR code. Meanwhile, in the current generation (generation Y, Z, and Alpha), the QRIS payment system is not only to support needs but has become a daily lifestyle. The QRIS payment system aligns with Talcott Parsons' theory of AGIL (adaptation, goal attainment, integration, and latency).